Determinants of residential dissonance: Implications for transit-oriented development in Brisbane. Issue 10 (25th November 2016) - Kamruzzaman, Md.; Baker, Douglas; Washington, Simon; Turrell, Gavin
ABSTRACT: Residential dissonance is the mismatch of land use patterns between individuals' actual and preferred neighborhood type. It is a threat to land-use-based policy interventions, such as transit-oriented development (TOD), which aims to enhance sustainable mobility behavior. Dissonants in TOD are more likely to use the car and less likely to use public transport. They do not naturally adjust their preferences according to their surrounding land use patterns and continue their predisposed travel behavior. Therefore, it is critical to identify dissonant groups to inform policy development to lessen the level of dissonance in TODs. This research identifies groups that are more likely to be dissonant in TOD/non-TOD areas in Brisbane. The living conditions of 6271 individuals were classified into TOD or non-TOD types based on a cluster analysis of built environmental factors. Individuals' preferred neighborhoods were also categorized into TOD and non-TOD types based on a factor analysis of travel attitudes and preferences. Four unique groups were identified (dissonants and consonants in both TOD and non-TOD areas) when respondents' actual and preferred neighborhood types were combined. Binary logistic regression analyses were employed to identify the determinants of residential dissonance in TOD/non-TOD areas. The results indicate that 30% of the respondents living in TOD areas are dissonants. Individuals who are male, have a car available at all times, and/or have poor health conditions were more likely to be dissonants in TOD areas in Brisbane.